Correlations, path coefficient analysis and phenotypic diversity of a West African germplasm of Kersting’s groundnut [Macrotyloma geocarpum (Harms) Maréchal & Baudet] - Akohoue, Felicien; Achigan-Dako, Enoch Gbenato; Coulibaly, Mariam; Sibiya, Julia (My University, 2019)
Providing the growing population with quality diet under the changing climate requires renewed efforts on the breeding of orphan grain legumes that need to be adequately characterized for accelerated cultivar development, particularly in sub- Saharan Africa where food and nutritional insecurity remains a critical challenge. In this study, the phenotypic diversity of a West African germplasm of Kersting’s groundnut was determined and the possibility for indirect selection explored. In total, 297 accessions collected across diverse ecological zones in Benin and Togo were assessed using 19 descriptors in two contrasting environments. Correlation and path coefficients analyses were performed to determine association patterns among variables. Hierarchical cluster analysis was carried out to group accessions having similar performance across locations. Based on the results, the diversity panel was categorized into four clusters with clusters 2 and 4 containing the best performing accessions. Significant moderate phenotypic correlation was detected between seed coat colour and days to 50% flowering (r = - 0.63). Likewise, significant and moderate to strong positive genetic correlations were observed between grain yield with number of seeds per pod (rg = 0.60), 100 seed weight (rg = 0.70), number of seeds per plant (rg = 0.96) and number of pods per plant (rg = 0.90). However, significant weak negative correlations were revealed among grain yield, days to 50% flowering (rg = - 0.32) and days to maturity (rg = - 0.30). Moreover, high direct effects were detected among grain yield and number of seeds per plant, 100 seed weight and days to 50% flowering. The findings imply that indirect selection for grain yield in Kersting’s groundnut, using 100 seed weight, number of seeds per plant and days to 50% flowering could be relevant to increase the efficiency of breeding programmes. Accessions 02_AF169, 02_AF51, 02_AF202, 02_AF222, 02_AF196, 02_AF100, 02_AF255, 02_AF216, 02_AF223 and 02_AF199 could also be used as parental lines for the development of high yielding varieties.
Keywords: Accession Indirect selection; Macrotyloma geocarpum Phenotypic diversity; West africa